2020
DOI: 10.3390/ma13225133
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Analysis and Stiffness Investigation of Extended End-Plate Connection

Abstract: Extended end-plate (EP) bolted connections are widely used in steel structures as moment-resisting connections. Most of these connections are semi-rigid or in other words flexible. The paper aims to study the behavior of such connections under the effect of column top-side cyclic loading using the finite element (FE) method. For semi-rigid connections, it is very vital to determine the moment-rotation relationship as well as the connection stiffness. These beam-column connections have been parametrically studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…В ряде научных публикаций представлены результаты исследований фланцевых узлов с учетом их жесткостных параметров [10][11][12][13][14][15][16][17][18][19][20]. Для определения жесткостных характеристик используются результаты расчетов конечно-элементных моделей и данные экспериментальных исследований.…”
Section: Introductionunclassified
“…В ряде научных публикаций представлены результаты исследований фланцевых узлов с учетом их жесткостных параметров [10][11][12][13][14][15][16][17][18][19][20]. Для определения жесткостных характеристик используются результаты расчетов конечно-элементных моделей и данные экспериментальных исследований.…”
Section: Introductionunclassified
“…In their research, Luo et al [21] constructed a finite element numerical model to investigate the behavior of an extended end-plate bolted connection subjected to cyclic loading from the column's top side. Through a parametric study, they found that the panel zone shear force plays a crucial role and significantly impacts the connection's stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to assess the fatigue behaviour of this type of joint, especially depending on the features that determine its operation (the lever lengths). There are numerous research papers on the behaviour of classic bolted connections [10][11][12][13][14][15][16][17], many of them focused on fatigue. For example, Zampieri et al [18] carried out a review of the fatigue resistance of bolted shear connections, Bartsch et al [19] performed an analysis of the fatigue strength of end plate connections with prestressed bolts, and Liu et al [20] showed a simplified modelling strategy based on continuous damage mechanics for the evaluation of cumulative fatigue damage in metal bolted joints.…”
Section: Introductionmentioning
confidence: 99%